Bridging regulation and reality: comparative study of Artificial Intelligence regulation in the financial sectors - Andistya Pratama; Dwi Ratna Indri Hapsari; Listiyani Wulandari (Faculty of Law, University of Muhammadiyah Malang, 2025)
This study compares AI regulations in Indonesia and Singapore's banking and fintech sectors, focusing on the gap between regulation and real-world conditions. Artificial Intelligence (AI) has become essential in the banking and fintech sectors, enhancing operational efficiency, detecting fraud, and performing risk analysis. However, the adoption of AI also poses challenges, particularly concerning regulation and consumer protection. The research employs normative or doctrinal methods with a comparative law approach. It evaluates various regulations issued by the Financial Services Authority (OJK) and Bank Indonesia (BI) in Indonesia, as well as the Monetary Authority of Singapore (MAS) in Singapore, specifically the FEAT and Veritas frameworks. The findings indicate that Singapore has proactively implemented principles of ethics, transparency, and accountability, while Indonesian regulations remain focused on consumer protection and operational stability, with a need for a more specific framework related to AI. The study concludes that harmonising regulation between innovation and consumer protection is crucial. Recommendations include the adoption of a regulatory sandbox and the implementation of ethical principles, such as FEAT, in Indonesia.